Entanglement Properties of a Higher-Integer-Spin AKLT Model with Quantum Group Symmetry - Arita, C.; Motegi, K. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
We study the entanglement properties of a higher-integer-spin Affleck-Kennedy-Lieb-Tasaki model with quantum group symmetry in the periodic boundary condition. We exactly calculate the finite size correction terms of the entanglement entropies from the double scaling limit. We also evaluate the geometric entanglement, which serves as another measure for entanglement. We find the geometric entanglement reaches its maximum at the isotropic point, and decreases with the increase of the anisotropy. This behavior is similar to that of the entanglement entropies.